Detailed Phenotype of GLA Variants Identified by the Nationwide Neurological Screening of Stroke Patients in the Czech Republic - Reková, Petra; Dostálová, Gabriela; Kemlink, David; Paulasová Schwabová, Jaroslava; Dubská, Zora; Vaneckova, Manuela; Mašek, Martin; Kodet, Ondřej; Poupětová, Helena; Mazurová, Stella; Rajdova, Aneta; Vlckova, Eva; et al. (Journal of clinical medicine, 2021)
Fabry disease (FD) is a rare X-linked disorder of glycosphingolipid metabolism caused by pathogenic variants within the alpha-galactosidase A (GLA) gene, often leading to neurological manifestations including stroke. Multiple screening programs seeking GLA variants among stroke survivors lacked detailed phenotype description, making the interpretation of the detected variant's pathogenicity difficult. Here, we describe detailed clinical characteristics of GLA variant carriers identified by a nationwide stroke screening program in the Czech Republic. A total of 23 individuals with 8 different GLA variants were included in the study. A comprehensive diagnostic workup was performed by a team of FD specialists. The investigation led to the suggestion of phenotype reclassification for the G325S mutation from late-onset to classical. A novel variant R30K was found and was classified as a variant of unknown significance (VUS). The typical manifestation in our FD patients was a stroke occurring in the posterior circulation with an accompanying pathological finding in the cerebrospinal fluid. Moreover, we confirmed that cornea verticillata is typically associated with classical variants. Our findings underline the importance of detailed phenotype description and data sharing in the correct identification of pathogenicity of gene variants detected by high-risk-population screening programs.
Keywords: screening programs; stroke; data sharing; Fabry disease; phenotype; GLA gene variants